Advances in Proteasome Enhancement by Small Molecules - Dare E. George; Jetze J. Tepe (Biomolecules, 2021)
The proteasome system is a large and complex molecular machinery responsible for the degradation of misfolded, damaged, and redundant cellular proteins. When proteasome function is impaired, unwanted proteins accumulate, which can lead to several diseases including age-related and neurodegenerative diseases. Enhancing proteasome-mediated substrate degradation with small molecules may therefore be a valuable strategy for the treatment of various neurodegenerative diseases such as Parkinson’s, Alzheimer’s, and Huntington’s diseases. In this review, we discuss the structure of proteasome and how proteasome’s proteolytic activity is associated with aging and various neurodegenerative diseases. We also summarize various classes of compounds that are capable of enhancing, directly or indirectly, proteasome-mediated protein degradation.